2014
DOI: 10.1128/jcm.02528-14
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time TaqMan PCR for Yersinia enterocolitica Detection Based on theailandfoxAGenes

Abstract: Y ersinia enterocolitica, a cause of emerging enteric infections, is a foodborne pathogen associated with various enteric and systemic syndromes, e.g., diarrhea, enteritis, and enterocolitis. Therefore, the detection of this pathogen has important significance. Previous real-time PCR for detection of Y. enterocolitica was primarily based on the ail gene; biotype 1A nonpathogenic strains were not included (1-3). However, recent studies (4,5) showed that biotype 1A ystB-positive strains are potentially pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Although TaqMan probes are more costly than SYBR green, the use of the sequence specific probes ensures high sensitivity, and specificity (Postollec et al, 2011; Law et al, 2014). Some target genes selected in the present study, as well as functional genes related to virulence or metabolism, have showed good specificity toward C. jejuni, Shigella spp., and Y. enterocolitica , when compared to standard methods (Wiemer et al, 2011; Wang et al, 2014; Van Lint et al, 2015). Three specific genes, namely, rfbE from E. coli O157:H7, hilA from S. enterica and prfA from L. monocytogenes were selected in our study to design primers and probes while fliC, invA , and hlyA were used in previous studies (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TaqMan probes are more costly than SYBR green, the use of the sequence specific probes ensures high sensitivity, and specificity (Postollec et al, 2011; Law et al, 2014). Some target genes selected in the present study, as well as functional genes related to virulence or metabolism, have showed good specificity toward C. jejuni, Shigella spp., and Y. enterocolitica , when compared to standard methods (Wiemer et al, 2011; Wang et al, 2014; Van Lint et al, 2015). Three specific genes, namely, rfbE from E. coli O157:H7, hilA from S. enterica and prfA from L. monocytogenes were selected in our study to design primers and probes while fliC, invA , and hlyA were used in previous studies (Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The virulence genes have been used as target genes for nucleic acid-based assays (Finlay and Falkow, 1997; Wiemer et al, 2011; Van Lint et al, 2015). Namely, flic, hlyA, rfbE were selected from E. coli O157:H7, invA, staG from Salmonella spp., ail, nuc from Staphylococcus aureus and foxA genes from Yersinia enterocolitica to design primers and probes in real-time TaqMan PCR assay (Ranjbar et al, 2014b; Wang et al, 2014; Ding et al, 2017; Zhou et al, 2017). Additionally, a simultaneous quantifying detection of V. parahaemolyticus and L. monocytogenes by TaqMan-based real-time PCR using primers and probes that target tlh and hlyA genes, respectively, was developed (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Real-time PCR of gene markers of Y. enterocolitica pathogenic strains was performed as previously described [29] with the exception that SYBR Green I dye was used instead of Taqman probes for monitoring the amplification.…”
Section: Methodsmentioning
confidence: 99%
“…and Yersinia detection, the fecal samples were mixed with phosphate-buffered saline and centrifuged at 500 g for 10 min, and the supernatant was used to extract the DNA using a TianGen DNA extraction kit (TianGen, Beijing, China) according to the manufacturer’s instructions. The DNA was subjected to qPCR with the primers and reaction conditions described in previous reports ( 34 , 35 ).…”
Section: Methodsmentioning
confidence: 99%